PENGARUH LAMA WAKTU PEMAKAIAN (USIA) DAN BENTURAN FISIK PADA KASET COMPUTER RADIOGRAPHY (CR)TERHADAP CITRA RADIOGRAFI - Siti Nur Hidayati; Ikhwanata (JRI (Jurnal Radiografer Indonesia), 2022)
Background: Computed Radiography (CR)is a radiographic image processing computer acquisition technology. In CR, the radiographic image results are stored in a special film cassette and expressed in the form of the gray level of the image pixels. The results of the radiographic image on the film cassette are then read by a scanner and then can be saved in the form of an image file, which can be a special digital film format called DICOM (Digital Imaging and Communication in Medicine). One of the disturbances that occur in the resulting CR image is artifact. The length of time used (age) of CR cassette can cause interference with the results of radiographic images. The longer the life of the CR cassette and the more frequent use of the CR cassette, the noise may appear in the radiographic image results. The condition of the CR cassette has a big effect on the formation od the image so that physical collision such as falling, regardless of grip or impact should be avoided when inserted into the CR reader. Methods: This type of research uses quantitative research with an experimental approach. The CR cassettes studied were 4 CR cassette with different sizes but the length of time used (age) was the same. All 4 CR cassette were exposes to the same exposure factor. The object used is the step wedge. The results of the radiographic images are evaluated subjectively by 5 respondents (radiographers) to draw conclusions. Results: The duration of use (age) of CR cassette is done properly and does not often occur, it will produce good radiographic image results and can be used to establish diagnoses. Physical impact on the CR cassette can results in artifact. Artifact contained in the results of CR images can interfere with diagnosis.